Electrochemical and computational study of the initiation step in the photoinduced electron transfer reaction between sulphur and selenide nucleophiles toward 1-bromonaphthalene - Bouchet, Lydia María (2016)
The initiation step of the photosubstitution reaction between 1-bromonaphthalene and a number of nucleophilic sulphur and selenium centred anions to afford 1-naphthylsulphide/selenide derivatives was investigated experimentally and by means of quantum chemical calculations. The frontier orbital energies of the anions were computed, and the values obtained agree with the lack of reactivity in the ground state. This model fails in accounting different reactivity of the anions toward the triplet state of 1-bromonaphthalene. Basicity and Eox were also calculated for all the anions finding a better agreement with the experimental reactivity and other measured properties such as pKa and oxidation potentials.